2021
DOI: 10.2147/pgpm.s301893
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C9*3/*3 Gene Expression Affects the Total and Free Concentrations of Valproic Acid in Pediatric Patients with Epilepsy

Abstract: Purpose To perform therapeutic drug monitoring (TDM) of total and free plasma valproic acid (VPA) concentrations in pediatric patients with epilepsy and to analyze related factors. Patients and Methods Pediatric epileptic patients treated in 2015–2019 in our hospital were assessed. Total and free plasma VPA concentrations were obtained by UPLC and LC-MS/MS, respectively. Regression analysis was performed to examine the associations of free plasma VPA with total plasma V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…However, these drug-gene interactions were marginal and not sufficient to justify their inclusion in official recommendations or drug labeling. In addition, numerous other polymorphisms annotated in the literature 18,63 and in FDA drug labels for valproate 138 , lamotrigine 139 and carbamazepine 140 as potentially relevant to drug metabolism did not show statistically significant…”
Section: Discussionmentioning
confidence: 92%
“…However, these drug-gene interactions were marginal and not sufficient to justify their inclusion in official recommendations or drug labeling. In addition, numerous other polymorphisms annotated in the literature 18,63 and in FDA drug labels for valproate 138 , lamotrigine 139 and carbamazepine 140 as potentially relevant to drug metabolism did not show statistically significant…”
Section: Discussionmentioning
confidence: 92%
“…Some reports have shown that CBPMs can inhibit the intestinal transporter and kill the enteric bacteria that can supply β‐glucuronidase, blocking the intestinal absorption of VPA (Mori et al, 2007). In addition, CBPMs have been confirmed to increase VPA's shift into erythrocytes and promote valproic glucuronide formation (Šíma et al, 2017; Wu et al, 2021; Yamamura et al, 2000). The other possible assumption involves the inhibition of acylpeptide hydrolase (APEH) activity by CBPMs, which causes a decrease in VPA β‐D‐glucuronide hydrolysis and therefore enhances the urinary elimination of VPA (Suzuki et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the serum concentrations of VPA metabolites (3‐OH‐VPA, 4‐OH‐VPA, 2‐ene‐VPA, 4‐ene‐VPA, 3‐keto‐VPA, and 2‐PGA) experienced varying degrees of decrease in epilepsy patients with VPA–CBPM comedication. This may be because the pharmacokinetics of VPA are disturbed by CBPMs, resulting in a reduction in total and free VPA concentrations (Wu et al, 2021). The metabolism of VPA involves three major metabolic pathways, namely the CYP pathway, UGT‐mediated pathway, and mitochondrial β‐oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings must be corroborated with pharmacogenetic studies by genotype, ethnicity, and miscegenation, as shown by Zhao et al (2020), who observed that the allelic variant UGT2B7 802C>T and age influence the concentration levels of VPA and suggested administering the anti-epileptic with caution in young patients who are poor metabolizers. In a recent study by Wu et al (2021) daily VPA doses and free drug concentrations were found to be significantly lower in patients with CYP2C9*3/*3 allelic variants versus CYP2C9*1/*3 groups and CYP2C9 *1/*1 (p<0.05), pharmacogenetic and TDM studies are recommended.…”
Section: Discussionmentioning
confidence: 99%